Grinding aid composition for wet crushing process
Patent Information
- Application Number
- KR1020260047690
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-03-17
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2046-03-17
Smart Images

Figure 112026032230057-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to the field of grinding process technology, and more specifically, to a grinding aid composition for a wet grinding process that can improve grinding efficiency while controlling the aggregation of fine powder, scale formation, and caking phenomena in a wet grinding process performed in grinding equipment such as a jaw crusher and a cone crusher. Background Technology
[0003] In general, various crushing equipment such as jaw crushers, cone crushers, and impact crushers are used in crushing processes for processing aggregates, minerals, or recycled aggregates, and wet crushing processes using water are widely applied to improve crushing efficiency or suppress dust generation.
[0004] In such wet grinding processes, fine particles generated during the grinding process are mixed with water and exist in a slurry state; during this process, problems such as aggregation of fine particles or the formation of scale inside the equipment may occur. Additionally, a phenomenon called caking may occur, where fine particles aggregate to form clumps.
[0005] If such scale formation or caking occurs, fine particles may adhere to the inside of the grinding equipment or the screen device, leading to reduced grinding efficiency and screen clogging; additionally, fine particles may re-attach to the surface of the ground particles, causing a deterioration in aggregate quality.
[0006] In particular, in the case of aggregates recovered from existing structures, such as recycled aggregates, fine particles and residual mortar components are easily generated during the grinding process. If these fine particles re-attach to the surface of the aggregate, the interfacial adhesion between the aggregate and the cement paste is reduced, which can lead to a decrease in the physical properties of the concrete, such as compressive strength, crack resistance, and durability.
[0007] To solve these problems, some technologies have been proposed that use grinding aids containing dispersants or wetting agents in the grinding process, but conventional grinding aids have been mainly focused on improving dispersibility, so there were limitations in effectively controlling scale formation and caking phenomena simultaneously.
[0008] In addition, while some additives are effective during the grinding process, there is a possibility that they may cause problems such as a decrease in initial strength or other physical properties of the concrete afterward.
[0009] Therefore, there is a need to develop a new grinding aid composition that can improve grinding efficiency and improve the surface condition of the ground aggregate while effectively controlling the aggregation, scale formation, and caking phenomena of fine particles in the wet grinding process. Prior art literature
[0011] Republic of Korea Patent Registration No. 10-222776 The problem to be solved
[0012] Accordingly, the present invention was devised to solve the above-mentioned problems and aims to provide a grinding aid composition for a wet grinding process that can improve grinding efficiency and improve the cleanliness of the aggregate surface by controlling scale formation and caking phenomena occurring in the wet grinding process. means of solving the problem
[0014] To achieve the above objective, the grinding aid composition for a wet grinding process of the present invention (hereinafter referred to as the "composition of the present invention") is characterized by comprising, for every 100 parts by weight of a polycarboxylate-based material, 10 to 30 parts by weight of HEDP, 10 to 30 parts by weight of a low molecular weight acrylic dispersant, 3 to 8 parts by weight of a nonionic surfactant, 50 to 150 parts by weight of water, 3 to 8 parts by weight of lignin sulfonate, 1 to 5 parts by weight of SAP, and 0.5 to 2 parts by weight of octyl palmitate.
[0015] delete
[0016] delete
[0017] delete
[0018] As an example, it is characterized by further including 0.1 to 1 weight part of magnesium carbonate.
[0019] As an example, it is characterized by further including 1 to 5 parts by weight of hyaluronic acid.
[0020] As an example, it is characterized by further including 0.5 to 2 parts by weight of calcium formate. Effects of the invention
[0022] According to the composition of the present invention, the aggregation of fine particles, scale formation, and caking phenomena that may occur in a wet grinding process can be effectively controlled.
[0023] In addition, the reattachment of fine particles generated during the grinding process can be suppressed to improve the surface cleanliness of the aggregate, thereby enhancing the interfacial adhesion between the aggregate and the cement paste.
[0024] In addition, when aggregate produced through the grinding process according to the present invention is applied to concrete, compressive strength and crack resistance can be improved. Brief explanation of the drawing
[0026] Figures 1 to 4 are photographs showing the composition of the present invention. Specific details for implementing the invention
[0027] Hereinafter, the structure and operation of the present invention will be explained in more detail with reference to the attached drawings. In describing the present invention, terms and words used in this specification and claims must be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to describe his invention in the best way possible.
[0029] The composition of the present invention is characterized by comprising, for every 100 parts by weight of a polycarboxylate-based agent, 10 to 30 parts by weight of HEDP, 10 to 30 parts by weight of a low molecular weight acrylic dispersant, 3 to 8 parts by weight of a nonionic surfactant, and 50 to 150 parts by weight of water.
[0030] Polycarboxylates act as the primary dispersion component of grinding aids and prevent fine particles generated during the aggregate crushing process from aggregating. Polycarboxylate polymers contain carboxyl groups (-COO) within their molecular structure. - It adsorbs to the particle surface and simultaneously imparts electrostatic repulsion and steric hindrance. As a result, aggregation between fine particles is suppressed, which improves grinding efficiency and reduces the phenomenon of fine powder reattaching to the aggregate surface.
[0031] Polycarboxylate-based materials such as polycarboxylate ethers, polycarboxylate copolymers, and methacrylic acid-based polycarboxylates may be applied.
[0032] The above HEDP (1-Hydroxyethylidene-1,1-diphosphonic acid) is a phosphate compound that functions to inhibit the formation of calcium carbonate and other inorganic scales by binding with calcium ions in process water.
[0033] In the aggregate crushing process, scale can form on the surface of the equipment due to calcium components contained in the process water and fine particles, and this scale can reduce the efficiency of the crushing equipment.
[0034] HEDP effectively inhibits scale formation by forming a complex with calcium ions, thereby suppressing scale nucleation and hindering crystal growth.
[0035] In the present invention, in order to secure a sufficient scale inhibition effect while preventing the hydration reaction from being delayed due to an excessive amount of phosphate-based components, it is preferable to use 10 to 30 parts by weight per 100 parts by weight of polycarboxylate-based components.
[0036] The above-mentioned low-molecular-weight acrylic dispersant adsorbs to the surface of fine particles to provide an additional dispersion effect and performs the function of inhibiting fine particle aggregation. In particular, the low-molecular-weight acrylic dispersant works in conjunction with polycarboxylate-based agents to inhibit the re-aggregation of fine particles, thereby enabling the maintenance of aggregate surface cleanliness and the improvement of grinding efficiency.
[0037] Polyacrylic acid, acrylic acid copolymers, acrylic acid-maleic acid copolymers, etc., can be used as low molecular weight acrylic dispersants.
[0038] In the present invention, it is preferable to use 10 to 30 parts by weight per 100 parts by weight of polycarboxylate-based material to ensure a sufficient dispersion effect.
[0039] The above-mentioned nonionic surfactant performs the function of improving the wettability of the surface of fine particles and aggregates. This allows fine particles to be dispersed more uniformly in the process water, and reduces the phenomenon of fine particles reattaching to the surface of aggregates during the grinding process.
[0040] In addition, nonionic surfactants play a role in improving the dispersibility of fine particles by reducing the interfacial tension between the fine particles and the process water.
[0041] Nonionic surfactants such as alkylphenol ethoxylates, fatty alcohol ethoxylates, and alkyl glucosides may be used.
[0042] In the present invention, in order to prevent excessive bubble generation while ensuring a sufficient wetting effect, it is preferable to use 3 to 8 parts by weight per 100 parts by weight of a polycarboxylate-based material.
[0043] The above water serves as a solvent to uniformly mix each component and prepare a liquid composition. In the present invention, considering the viscosity and handling properties of the composition, it is preferable to use 50 to 150 parts by weight per 100 parts by weight of the polycarboxylate-based water.
[0044] In addition, the composition of the present invention may further include lignosulfonate.
[0045] Lignin sulfonates are anionic polymers produced by sulfonating woody lignin, and are designed to perform a dispersion function while simultaneously inhibiting the formation of inorganic scale through interaction with metal ions.
[0046] In the aggregate crushing process, scale may form on the equipment and the surface of fine particles due to calcium components in the process water. This scale can induce the aggregation of fine particles and cause them to re-attach to the aggregate surface. Consequently, the cleanliness of the aggregate surface deteriorates, and the interfacial adhesion between the aggregate and the cement paste decreases, which can lead to a reduction in the compressive strength and crack resistance of the concrete.
[0047] Accordingly, in the present invention, by adding lignin sulfonate, scale formation is suppressed and the dispersibility of fine particles is improved, thereby improving the cleanliness of the aggregate surface. Consequently, the interfacial adhesion between the aggregate and the cement paste is enhanced, which can improve the compressive strength and crack resistance of the concrete.
[0048] Preferably, the lignin sulfonate is appropriately formulated in a range of 3 to 8 parts by weight per 100 parts by weight of the polycarboxylate system.
[0049] On the other hand, when only lignin sulfonates are added, the cement hydration reaction is partially delayed, which may increase the time the concrete remains in the plastic state; consequently, if surface moisture evaporation continues in this state, there is a problem that the likelihood of plastic shrinkage cracks occurring increases.
[0050] Accordingly, the present invention provides an example in which SAP (Super Absorbent Polymer) is further included.
[0051] SAP can provide an internal curing effect by storing moisture internally and releasing it when the moisture content of the concrete decreases; consequently, it can suppress plastic shrinkage by reducing capillary tension. Furthermore, SAP can reduce crack formation by stabilizing the internal moisture distribution of the concrete and inhibiting self-desiccation.
[0052] Preferably, it is appropriate to incorporate 1 to 5 parts by weight of SAP per 100 parts by weight of polycarboxylate-based.
[0053] In addition to this, the present invention provides an example in which octyl palmitate is further included in addition to lignin sulfonate and SAP.
[0054] Octyl palmitate is a long-chain fatty acid ester compound that performs the function of reducing surface tension and improving the wettability of fine particles and aggregate surfaces.
[0055] While the aforementioned SAP provides an internal curing effect by controlling moisture inside the concrete, octyl palmitate can play a role in mitigating the rate of moisture evaporation from the concrete surface.
[0056] In other words, while SAP performs the function of inhibiting moisture loss within the concrete, octyl palmitate performs the function of inhibiting moisture evaporation from the concrete surface, allowing the two materials to act complementarily.
[0057] In this way, when internal moisture retention and surface moisture retention are achieved simultaneously, plastic shrinkage of concrete can be suppressed more effectively, and consequently, resistance to plastic shrinkage cracking can be further improved.
[0058] Preferably, octyl palmitate is appropriately formulated in an amount of 0.5 to 2 parts by weight per 100 parts by weight of polycarboxylate-based.
[0059] Meanwhile, the addition of SAP can cause fine particles that have absorbed moisture to aggregate, leading to caking. This caking causes the fine particles to re-attach to the aggregate surface, which can reduce the interfacial adhesion between the aggregate and the cement paste. Consequently, the compressive strength of the concrete may decrease.
[0060] Accordingly, the present invention provides an example in which magnesium carbonate is added to improve the flowability of the powder and suppress aggregation between particles, thereby effectively controlling caking. In other words, the compressive strength of the concrete is further enhanced through the control of caking by the addition of magnesium carbonate.
[0061] Preferably, magnesium carbonate is appropriately formulated in an amount of 0.1 to 1 weight part per 100 weight parts of the polycarboxylate-based material.
[0062] Meanwhile, as previously mentioned in the present invention, scale formation that may occur during the aggregate crushing process can be suppressed to a certain level by the action of polycarboxylate-based, HEDP, and low molecular weight acrylic-based dispersants.
[0063] However, depending on process conditions, scale formation may not be completely controlled, which may cause fine particles to remain on or reattach to the aggregate surface, thereby reducing interfacial adhesion between the aggregate and the cement paste.
[0064] Accordingly, the present invention provides an example in which hyaluronic acid is additionally included to improve the interaction between the aggregate surface and cement paste particles and to increase interfacial bonding strength, thereby effectively compensating for the problem of reduced interfacial adhesion that may occur due to residual scale.
[0065] Hyaluronic acid is a high-molecular-weight polysaccharide containing multiple carboxyl and hydroxyl groups, possessing excellent water affinity and the ability to adsorb onto the surfaces of various inorganic particles. This hyaluronic acid adsorbs onto the aggregate surface and the constituent particles of the cement paste to form a thin, water-friendly polymer layer, thereby playing a role in improving the interfacial bonding strength between the aggregate and the cement paste.
[0066] Accordingly, the interface transition zone (ITZ) between aggregate and cement paste can be formed more stably during concrete manufacturing, and as a result, contributes to improving the compressive strength of the concrete.
[0067] Preferably, hyaluronic acid is appropriately formulated in an amount of 1 to 5 parts by weight per 100 parts by weight of polycarboxylate-based.
[0068] On the other hand, when polymeric materials such as hyaluronic acid are added, the hydration reaction may be partially delayed by the polymer layer adsorbed on the surface of cement particles, which may lead to a problem of reduced early strength development of the concrete.
[0069] Accordingly, the present invention provides an example in which calcium formate is further added. By including the calcium formate, the initial hydration delay that may occur due to the addition of hyaluronic acid can be compensated for, thereby preventing a decrease in the initial strength of the concrete.
[0070] Preferably, the calcium formate is appropriately formulated in a range of 0.5 to 2 parts by weight per 100 parts by weight of the polycarboxylate-based.
[0072] Embodiments of the present invention will be explained through the following experimental examples.
[0073] First, to manufacture recycled aggregate, concrete waste generated from waste concrete structures was collected and processed through crushing and screening to prepare recycled coarse aggregate. The prepared recycled coarse aggregate used had a particle size range of 5 mm to 20 mm, and screening and washing processes were performed to remove foreign substances such as wood, plastic, and metal. Subsequently, pretreatment was carried out by natural drying at room temperature to achieve a surface-dry state in order to minimize the impact of excessive moisture on the aggregate surface.
[0074] The recycled aggregate prepared in this manner was fed into a crushing device to perform a crushing process. A rotary crusher was used as the crushing device, and the amount of recycled aggregate fed into one crushing process was set to approximately 20 kg. A crushing aid was used at a concentration of 0.05 weight percent relative to the recycled aggregate, and the crushing aid was diluted with water and uniformly sprayed onto the surface of the aggregate, then mixed for approximately 2 minutes to ensure that the crushing aid was sufficiently coated on the surface of the aggregate.
[0075] Subsequently, the aggregate was fed into a grinder and ground for approximately 15 minutes, ensuring that mortar components and fine particles attached to the surface of the aggregate were effectively removed during the grinding process. After the grinding was completed, the aggregate was sieved to remove excess fine particles and used as coarse aggregate in each of the following samples.
[0076] Recycled aggregate was prepared by applying the grinding aids of Examples 1 to 7 below under the conditions described above, and the grinding efficiency was tested as follows.
[0078] <Example 1>
[0079] For every 100 parts by weight of a polycarboxylate-based compound, 20 parts by weight of HEDP, 15 parts by weight of a low molecular weight acrylic dispersant, 5 parts by weight of a nonionic surfactant, and 100 parts by weight of water were mixed.
[0081] <Example 2>
[0082] It was identical to Example 1, except that 4 parts by weight of lignin sulfonate were added.
[0084] <Example 3>
[0085] It is identical to Example 2, but with an additional 2 parts by weight of SAP added.
[0087] <Example 4>
[0088] It was identical to Example 3, except that 1 weight part of octyl palmitate was added.
[0090] <Example 5>
[0091] It was the same as Example 4, but with an additional 0.3 parts by weight of magnesium carbonate added.
[0093] <Example 6>
[0094] It was identical to Example 1, except that 3 parts by weight of hyaluronic acid were added.
[0096] <Example 7>
[0097] It was the same as Example 6, except that 0.5 parts by weight of calcium formate were added.
[0099] Grinding efficiency was evaluated based on the amount of fine powder generated during the grinding process and the degree of screen clogging.
[0100] Specifically, the aggregates before and after the grinding process were sieve-analyzed to measure the amount of fine particles of 0.075 mm or less and the amount of screen clogging occurring during the grinding process. The results are shown in Table 1 below. Meanwhile, in Table 1 below, the comparative example is the case where no grinding aid was added.
[0102] division Unit energy (kWh / t) 0.075mm Generation Amount (%) Screen clogging amount (g) Comparative example 7.8 2.4 120 Example 1 7.1 2.1 85 Example 2 6.9 2.0 72 Example 3 6.8 2.0 95 Example 4 6.8 1.9 90 Example 5 6.6 1.9 60 Example 6 7.0 2.1 84 Example 7 7.1 2.1 82
[0104] Looking at Table 1 above, it can be seen that compared to the comparative example, the examples show a tendency for reduced unit energy consumption, maintained fine particle content at an appropriate level, and reduced screen clogging. This is believed to be because the dispersibility of fine particles is improved and caking formation is suppressed by the action of the grinding aid.
[0105] When comparing Example 1 and Example 2, it can be seen that the amount of screen clogging is reduced in the case of Example 2, which is believed to be because scale formation during the process is suppressed and the aggregation of fine particles is reduced by the addition of ligninsulfonate in Example 2.
[0106] When comparing Example 2 and Example 3, it can be seen that Example 3 shows a tendency for screen clogging to increase, which is believed to be because fine particles that absorbed moisture due to the addition of SAP aggregated together, causing some increase in caking.
[0107] Meanwhile, when comparing Example 3 and Example 5, it can be seen that the amount of screen clogging in Example 5 is significantly reduced. This is believed to be because the formation of caking was suppressed as physical gaps between particles were formed due to the additional inclusion of magnesium carbonate in Example 5.
[0108] Therefore, from the above results, it is confirmed that in the case of Example 5 containing magnesium carbonate, caking formation is effectively suppressed during the grinding process, resulting in the best grinding efficiency.
[0109] Next, samples were prepared according to the formulation in Table 2 below, and flow (KS F 2594), compressive strength (KS F 2405), and crack resistance (KS F 2424, 28 days) were tested, and the results are shown in Table 3.
[0111] division W / C Air volume (%) OPC(kg / m³) S(㎏ / ㎥) G(㎏ / ㎥) W(㎏ / ㎥) combination 0.45 4.5±1.0 350 750 1,000 255
[0112] S: Natural sand, G: Aggregate manufactured according to each example
[0114] division FLOW(mm, 30 min) Rate of change in length (X 10 -6 ) Compressive strength (MPa) 1 day 3 days 7 days 28th Example 1 165 / 150 -610 14 24 30 38 Example 2 168 / 152 -595 13 25 31 39 Example 3 170 / 158 -520 12 24 30 38 Example 4 173 / 160 -500 12 24 29 39 Example 5 172 / 160 -495 13 25 32 41 Example 6 160 / 145 -600 11 23 31 41 Example 7 161 / 146 -610 13 25 32 41
[0116] Looking at Table 3 above, it can be seen that Examples 1 to 7 all exhibit relatively good flow values. This is attributed to the fact that fine particles attached to the surface of the aggregate are effectively removed by the action of the grinding aid, and the cleanliness of the aggregate surface is improved, thereby improving the fluidity of the concrete.
[0117] When comparing Example 1 and Example 2, it can be seen that the flow value in Example 2 tends to increase slightly. This is because the addition of lignin sulfonate improves the dispersibility of fine particles and partially suppresses scale formation on the aggregate surface, thereby improving the workability of the concrete.
[0118] When comparing Example 2 and Example 3, it can be seen that Example 3 shows a tendency for flow retention to improve somewhat, which is believed to be because the moisture distribution inside the concrete is stabilized and moisture loss is partially suppressed by the addition of SAP.
[0119] When comparing Example 3 and Example 4, it can be seen that the flow value in Example 4 shows a tendency to increase slightly, which is attributed to the addition of octyl palmitate improving the wettability of the aggregate and fine powder surfaces, thereby improving the fluidity of the concrete.
[0120] Meanwhile, when comparing Example 1 and Example 6, it can be seen that the flow value in Example 6 tends to decrease slightly, which is believed to be due to the increase in viscosity of the concrete mixture caused by the addition of hyaluronic acid.
[0121] When comparing Example 6 and Example 7, it can be seen that the flow value of Example 7 remains at a level similar to that of Example 6. This is believed to be because the relatively small amount of calcium formate added does not significantly affect the fluidity of the concrete mixture.
[0122] When comparing Example 1 and Example 2 in terms of crack resistance, it can be seen that Example 2 shows a tendency for the rate of change in length to decrease slightly. This is believed to be because the addition of lignin sulfonate inhibits scale formation on the aggregate surface and improves interfacial adhesion between the aggregate and the cement paste.
[0123] When comparing Example 2 and Example 3, it can be seen that the rate of change in length is significantly reduced in the case of Example 3. This is believed to be because the moisture stored inside the concrete is gradually released due to the addition of SAP, thereby exhibiting an internal curing effect.
[0124] When comparing Example 3 and Example 4, it can be seen that the rate of change in length is further reduced in the case of Example 4. This is believed to be because the addition of octyl palmitate partially suppresses moisture evaporation from the concrete surface, thereby further reducing drying shrinkage.
[0125] When comparing Example 4 and Example 5, it can be seen that Example 5 exhibits the smallest value for the rate of change in length. This is believed to be because the addition of magnesium carbonate suppresses caking and maintains a uniform aggregate surface condition, thereby forming a more stable internal structure of the concrete.
[0126] When comparing Example 1 and Example 2 in terms of compressive strength, it can be seen that Example 2 shows a tendency for slightly increased compressive strength. This is believed to be because the addition of lignin sulfonate suppresses scale formation on the aggregate surface and reduces the aggregation of fine particles, thereby forming a more stable interfacial bond between the aggregate and the cement paste.
[0127] When comparing Example 3 and Example 5, it can be seen that Example 5 exhibits the highest compressive strength value. This is believed to be because the addition of magnesium carbonate suppresses caking, resulting in a more uniform aggregate surface condition during the grinding process, and consequently, a more dense internal concrete structure.
[0128] Meanwhile, when comparing Example 1 and Example 6, it can be observed that in the case of Example 6, the compressive strength (1 day, 3 days) tends to decrease slightly at the initial age. This is believed to be because the addition of hyaluronic acid caused a polymer layer to form on the surface of the cement particles, thereby partially delaying the initial hydration reaction. On the other hand, it can be observed that the compressive strength of Example 6 tends to increase as the age increases (7 days, 28 days). This is believed to be because hyaluronic acid improved the interfacial bonding strength between the aggregate and the cement paste, thereby forming a more dense internal structure of the concrete.
[0129] When comparing Example 6 and Example 7, it can be seen that the initial compressive strength of Example 7 increased compared to Example 6. This is believed to be because the hydration reaction of the cement was promoted by the addition of calcium formate, thereby improving the development of the initial strength.
[0131] From the above description, those skilled in the art will understand that various changes and modifications are possible within the scope of the technical concept of the present invention. Accordingly, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.
Claims
Claim 1 A grinding aid composition for a wet grinding process, characterized by comprising, based on 100 parts by weight of a polycarboxylate-based agent, 10 to 30 parts by weight of HEDP, 10 to 30 parts by weight of a low molecular weight acrylic dispersant, 3 to 8 parts by weight of a nonionic surfactant, 50 to 150 parts by weight of water, 3 to 8 parts by weight of lignin sulfonate, 1 to 5 parts by weight of SAP, and 0.5 to 2 parts by weight of octyl palmitate. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A grinding aid composition for a wet grinding process, characterized in that, in claim 1, it further comprises 0.1 to 1 weight part of magnesium carbonate. Claim 6 A grinding aid composition for a wet grinding process, characterized in that, in claim 1, it further comprises 1 to 5 parts by weight of hyaluronic acid. Claim 7 A grinding aid composition for a wet grinding process, characterized in that, in claim 6, it further comprises 0.5 to 2 parts by weight of calcium formate.
Citation Information
Patent Citations
Maufacturing methode of loess mortar
KR1020050077452A
A Grinding aid
KR1020180050852A
A kind of polishing composition and its use
KR1020250044903A
Ultra High Density Concrete, Manufacturing Method of such Concrete, Concrete Member made by such Concrete, and Manufacturing Method of such Concrete Member
KR102255042B1
Wet press concrete slab manufacturing
WO2016081080A1
